Electrospinning Synthesis of Porous CoWO4 Nanofibers as an Ultrasensitive, Nonenzymatic, Hydrogen‐Peroxide‐Sensing Interface with Enhanced Electrocatalysis. Issue 12 (24th August 2015) - Liao, Sheng‐Hui; Lu, Shi‐Yu; Bao, Shu‐Juan; Yu, Ya‐Nan; Yu, Ling
Abstract: In this work, porous WO3, Co3 O4, and CoWO4 nanofibers (NFs) were fabricated by using an electrospinning technique followed by high‐temperature calcination. The different NFs were used to modify biosensor electrodes and detect H2 O2 without the help of an enzyme. The electrochemical results indicated that the CoWO4 NF‐based sensor presented a remarkable electrocatalytic activity towards H2 O2 oxidation, including lower redox potential, lower detection limit, fast response, as well as the widest linear range among our designed biosensors of this type. Furthermore, we found that the ideal test potential of a nonenzymatic biosensor is closely dependent on the composition of the detected electrode surface, and the test potential has a great effect on the detection linear range of nanomaterial‐based biosensors. The results of this work provide a new way to explore excellent nanomaterials for modifying nonenzymatic biosensor electrodes. Abstract : You spin me right round : Porous WO3, Co3 O4, and CoWO4 are fabricated by using an electrospinning technique followed by high‐temperature calcination. The different NFs are used to modify biosensor electrodes and detect H2 O2 without the help of enzymes. The results provide a new insight that enables excellent nonenzymatic biosensors to be explored.